Formação continuada de professores de educação física da rede municipal de ensino de Cuiabá-MT : entre o ideal e o vivido - Batista, Danielle (2015)
The present study aims to investigate the design and use of continuing education in the development of teaching methods of physical education teachers. Under the understanding that continuing education is an essential process in the construction of being a teacher, it is essential to understand its influence on the professional career of physical education teachers of local schools of Cuiabá, MT for future training policies. This study is characterized as a qualitative and descriptive, and its research universe two municipal schools in the northern region of Cuiabá, MT, and the participants are two teachers of Physical Education who work in these schools and participated in the research project "Profile and activities professional of physical education teachers from Cuiabá municipal school system: study, analysis and proposals for continuing education ", developed between 2009 and 2012. Moreover, since 2013 they participate in continuing education project offered by the Faculty of Physical Education teachers of municipal schools of Cuiabá, MT. The data collection instrument was a structured interview containing two scripts, the first diagnostic to identify the formative path and the investigated teacher performance and the second, a semi-structured interview with 17 questions based on objectives related to the searched subject. Another instrument used was the documentary analysis of teaching plans for teachers to identify the technical and methodological elements and used in theoretical and practical activities. Finally, systematic observation recorded as professional practices are organized and take place from the possibilities presented in the continuing education and declared by teachers. After analyzing the data it was concluded that training is an essential process to become a teacher, which is conceived as a mediator in the development of knowledge and subject to constant training. In this respect, the whole construction process is directly reflected in its action within their workplace, the experience, production and sharing of knowledge with the subjects of their action. Also we identified that the school is a key space for teacher training because it can enhance the knowledge of experience and pay attention to the different stages of teacher professional development. This condition permeates the teaching trajectory and reflects considerably in all its actions. By evidencing the lives of teachers and give voice to them, we find that both have a time of relevant experience with activities in Basic Education, showing part of your reality. They have some essential features to the context of promoting the knowledge we bring an appropriate reflection on teaching. However, we found that the reality of the profession, especially physical education within the school, need to modify their paradigms. Finally, we understand that the process of continuing education that the teachers have started feeling the fundamental redefinition of its shares, thus building an identity that changed and evidenced physical education as an essential component for the formation of children.